(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper deals with the cyber crime & its realistic facts which blocked our working capability, efficiency & revealed the privacy of victims. This paper also deals with the futuristic cyber crime & its prevention. We are very thankful to Prof. Sitanshu Ray for his tireless support and his lucid way of explaining us the salient points really helped us to write this paper.